2020
DOI: 10.3390/ijms21020440
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Platinum Nanoparticle-Induced Cytotoxicity, Apoptosis, Inflammatory Response, and Transcriptomic and Molecular Pathways in Human Acute Monocytic Leukemia Cells

Abstract: The thermoplasmonic properties of platinum nanoparticles (PtNPs) render them desirable for use in diagnosis, detection, therapy, and surgery. However, their toxicological effects and impact at the molecular level remain obscure. Nanotoxicology is mainly focused on the interactions of nanostructures with biological systems, particularly with an emphasis on elucidating the relationship between the physical and chemical properties such as size and shape. Therefore, we hypothesized whether these unique anisotropic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 112 publications
(166 reference statements)
1
21
0
Order By: Relevance
“…We have previously shown that different shapes and sizes of platinum nanoparticles decrease CAT activity in THP-1 cells. 40 , 82 Similarly, the level of SOD was significantly lower in cells treated with PdNPs (10 μmol) and CSP (8 μmol) than in control cells, whereas GW4869-treated cells showed no significant effect (18 μmol) on CAT activity compared to the control (20 μmol) ( Figure 6D ). The concentrations of CAT and SOD were reportedly significantly compromised in PdNP-exposed human ovarian cancer cells, 37 human cervical cancer cells, 59 human breast cancer cells, 60 and human lung epithelial adenocarcinoma cells.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…We have previously shown that different shapes and sizes of platinum nanoparticles decrease CAT activity in THP-1 cells. 40 , 82 Similarly, the level of SOD was significantly lower in cells treated with PdNPs (10 μmol) and CSP (8 μmol) than in control cells, whereas GW4869-treated cells showed no significant effect (18 μmol) on CAT activity compared to the control (20 μmol) ( Figure 6D ). The concentrations of CAT and SOD were reportedly significantly compromised in PdNP-exposed human ovarian cancer cells, 37 human cervical cancer cells, 59 human breast cancer cells, 60 and human lung epithelial adenocarcinoma cells.…”
Section: Resultsmentioning
confidence: 92%
“…Similarly, metal nanoparticles such as silver induce oxidative stress in male somatic and spermatogonial stem cells, 75 F9 teratocarcinoma stem cells, 76 mouse embryonic fibroblast cells, 77 and various types of human cancer cells including human breast 78 , 79 and human lung cancer cells 80 , 81 via the generation of ROS. Similarly, platinum nanoparticles cause oxidative stress in THP-1 cells, 82 and PdNPs induce oxidative stress and eventual cell death in human ovarian cancer cell lines A2780 37 and SKOV3. 61
Figure 5 Effect of PdNPs on oxidative stress markers.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, cells pre-treated with NAC showed that caspase-3 levels were equal to those in the control, indicating that NAC inhibits the PtNPs- or C6-cer-or CSP induced apoptosis. Previous studies have demonstrated that PtNPs or platinum nanocomposites induce apoptosis through the activation of caspase-3 in various types of cancer cells, including prostate cancer cells, 39 human acute monocytic leukemia cells 94 human hepatic cancer cells, 95 and human neuroblastoma cancer cells. 41 Ceramide triggers caspase-3 activation and induces apoptosis in A549 lung cancer cells.…”
Section: Resultsmentioning
confidence: 99%